Faecal Glucocorticoid Metabolites and Hair Cortisone/Cortisol Measurements in Domestic Pigs Exposed to Road Transportation and Dexamethasone Treatment - Asencio, Camila J.; Palme, Rupert; Ferrari, Héctor Ricardo; Lattanzi, Mariano Luis; Eguizábal, Gabina V.; Busso, Juan Manuel (MDPI, 2024)
Pig homeostasis is challenged by stressful production practices, like road transportation. Glucocorticoids (GCs) are mediators of reactive homeostasis, and their concentrations are frequently used as a stress indicator. The adrenocortical activity of fattening female and castrated male pigs was monitored over a 5-day longitudinal study. A bi-factorial experimental design was applied on day 2; 18 pigs in pen 1 were transported for 3 h (T; 1.2 m2/pig), and 18 pigs were kept in pen 2 (NT). Ten pigs from each pen were treated with dexamethasone (T-D or NT-D), and eight with saline solution (T-SS or NT-SS). Adrenocortical activity was assessed by measuring the levels of faecal glucocorticoid metabolites (FGMs) and hair cortisol and cortisone. In T-SS pigs, the level of FGMs was higher after transportation than in NT-SS pigs. The level of FGMs of T-D pigs initially increased but then reached similar levels to those of NT-SS sooner than T-SS. In contrast, hair cortisol and cortisone did not respond to the treatments. Nevertheless, the hair cortisone/cortisol ratio increased due to transport and decreased after dexamethasone administration. Daily faecal sampling proved still more reliable than 60-day hair sampling for assessing adrenocortical activity. Transported pigs recovered their adrenocortical baseline levels within 24 h. Dexamethasone attenuated the response to transport.